Workshop environment heterogeneity shaped the microbiome and metabolome profiles during Xiasha round of Jiangxiangxing Baijiu - Cailing Wang; Chenyao Li; Zhiqiang Bin; Guojun Zhu; Shaopei Tang; Jinyu Zhang; Yefu Chen; Dongguang Xiao; Xuewu Guo (Food Chemistry: X, 2024)
Workshop with different fermentation years plays an essential role in the yield and quality of Baijiu. In actual production, the quality of base Baijiu in newly built workshop is inferior to the older one. In this study, the microbiota of workshop environment and fermentation process from two workshops namely N (ferment 2 years) and O (ferment 20 years) and flavor compounds were studied during Xiasha round. Results showed workshop O accumulated more environmental microorganisms and fungi including P. kudriavzevii, Wickerhamomyces anomalus and Saccharomyces sp mainly came from ground. Yeasts including Pichia, Cyberlindnera, Wickerhamomyces and Candida were responsible for flavor substances formation in O while Saccharopolyspora was in N. This study for the first time explored the reasons for the brewing differences among N and O workshop from perspectives of workshop environment, microbial community and flavor substances, providing new ideas for guiding production as well as improvement of Baijiu quality.